Derivatives - Somanathan, T. V.; Nageswaran, V. Anantha; Gupta, Harsh, 1986- (Cambridge : Cambridge University Press, 2018)
This book provides a comprehensive but concise treatment of the subject of derivatives. It focuses on making essential concepts accessible to a wider audience. The book eschews complicated mathematics and high school level mathematics is sufficient to understand it. It describes and explains various derivative instruments, their use and pricing, and the functioning of derivative markets. It uses a large number of examples to elucidate concepts and illustrate their real-life application. A distinguishing feature of the book is that it goes beyond the narrow perspective of derivative traders and investors and takes a broader approach which enhances its appeal to a range of readers. This book will be useful for students in the fields of economics, econometrics, derivatives, and finance and financial professionals, bankers and investors.
Title from publisher's bibliographic system (viewed on 09 Aug 2019).
Keywords: Derivative securities